Postavení Islandu v mezinárodním obchodě - Bialožytová, Tereza (Vysoká škola ekonomická v Praze, 2012)
Cílem této práce je analyzovat postavení Islandu v mezinárodním obchodě, s ohledem na jeho aktuální ekonomickou situaci a vývoj hospodářské situace od roku 2008, kdy na Island dolehla hospodářská krize. V práci jsou rovněž analyzována odvětví, která jsou pro Island typická. Práce také rozebírá Island jako kandidáta na členství v Evropské Unii. V této části jsou charakterizovány problémové body přístupového jednání. Dále se práce věnuje obchodním vztahům Islandu s Českou republikou. The aim of this bachelor thesis is to analyze the position of Iceland in the international trade, considering present economic situation and development of economic situation after the year 2008. In the year 2008 Iceland was hit by economic crisis with its full force. There are also analyzed sectors in this thesis, which are for Iceland typical. The thesis analyzes Iceland as a candidate for membership in the European Union as well. Problematic points of the accession negotiations are described in this part. After that it is focused on business relations between the Czech republic and Iceland.